2019
DOI: 10.25002/tji.2019.1027
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Overcome Neuroendocrine Immune Deficits in Aging: Role of Neuroendocrine-Immune Modulators and Bioactive Plant Extracts

Abstract: The neuroendocrine immune network functions in a delicate balance during health and the ability to maintain this balance through disease affects the outcome of the disease. During aging, there is a general decline in each of these systems that reflects on their synergistic functions and affect homeostasis leading to age-associated diseases including cancer, autoimmunity and degenerative diseases. Immunomodulation by estrogen through cyclic menstrual variations and precipitous decline during reproductive aging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Comparative analysis of age-related immunosenescence reversal strategies using synthetic drugs and natural remedies has shown significant immunomodulatory effects through modulation of MAPK and NF-kB signaling cascades in middle-aged and elderly rats. [299] The implications of the B. monnieri extract on the in-vitro ICR mice immune system study showed that the extract slightly suppressed the proliferation of splenocytes and decreased the proliferation of T-lymphocytes but slightly increased the activity of the lysosomal enzyme, suggesting a poor effect on phagocytic activation. [300]…”
Section: Immune Modulationmentioning
confidence: 99%
“…Comparative analysis of age-related immunosenescence reversal strategies using synthetic drugs and natural remedies has shown significant immunomodulatory effects through modulation of MAPK and NF-kB signaling cascades in middle-aged and elderly rats. [299] The implications of the B. monnieri extract on the in-vitro ICR mice immune system study showed that the extract slightly suppressed the proliferation of splenocytes and decreased the proliferation of T-lymphocytes but slightly increased the activity of the lysosomal enzyme, suggesting a poor effect on phagocytic activation. [300]…”
Section: Immune Modulationmentioning
confidence: 99%
“…As gonadal hormones, both androgens and estrogens can improve immunity [29,30]. In particular, estrogen can alter the immune response by binding to specific receptors on immune cells, resulting in their proliferation, and they play a feedback regulatory role on the hypothalamic-pituitary axis [29,31].…”
Section: Neuroendocrine-immune Regulatory Networkmentioning
confidence: 99%